Prevalence and temporal trends of prostate diseases among inpatients with cardiovascular disease: a nationwide real-world database survey in Japan - Kaneta, Kohei; Tanaka, Atsushi; Nakai, Michikazu; Sumita, Yoko; Kaneko, Hidehiro; Noguchi, Mitsuru; Node, Koichi (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Benign prostate hyperplasia (BPH) and prostate cancer (PCa) are major prostate diseases that potentially share cardiometabolic risk factors and an elevated risk for cardiovascular disease (CVD). However, the prevalence of prostate diseases among patients with established CVD remains unclear. Materials and methods: This nationwide retrospective study assessed the prevalence and temporal trend of prostate diseases (i.e. BPH or PCa) among patients hospitalized for CVDs in Japan. We used a claims database (the Japanese Registry of All Cardiac and Vascular Diseases–Diagnosis Procedure Combination), which included data on 6,078,487 male patients recorded from 1,058 hospitals between April 2012 and March 2020. We conducted the Cochran–Armitage trend test and calculated the adjusted odds ratio (aOR) with 95% confidence intervals (CIs). Results: The prevalence of prostate diseases over the entire study period was 5.7% (BPH, 4.4%; PCa, 1.6%). When dividing the overall cohort into age categories (<65, 65–74, and ≥75 years old), the prevalence was 1.1%, 4.7%, and 9.9%, respectively (P for trend <0.05). In addition, the annual prevalence showed a modest increasing trend over time. Patients admitted for heart failure (HF) were significantly associated with a higher incidence of coexisting prostate diseases than those admitted for non-HF causes (aOR 1.02 [95% CI, 1.01–1.03]) or acute coronary syndrome (aOR 1.19 [95% CI, 1.17–1.22]). Conclusions: The nationwide real-world database revealed that the prevalence of prostate diseases is increasing among patients hospitalized for CVD, particularly HF. Attention to detailed causality and continued surveillance are needed to further clarify the clinical characteristics of prostate diseases among patients with CVD.